A carnival of snackery diaries (2003-2020) - Sedaris, David 1956- (Little, Brown and Company, 2021)
"There's no right way to keep a diary, but if there's an entertaining way, David Sedaris seems to have mastered it. If it's navel-gazing you're after, you've come to the wrong place; ditto treacly self-examination. Rather, his observation turn outward: a fight between two men on a bus, a fight between two men on the street, pedestrians being whacked over the head or gathering to watch as a man considers leaping to his death. There's a dirty joke shared at a book signing, then a dirtier one told at a dinner party -- lots of jokes here. Plenty of laughs. These diaries remind you that you once really hated George W. Bush, and that not too long ago, Donald Trump was just a harmless laughingstock, at least on French TV. Time marches on, and Sedaris, at his desk or on planes, in hotel dining rooms and odd Japanese inns, records it. The entries here reflect an ever-changing background -- new administrations, new restrictions on speech and conduct. What you can say at the start of the book, you can't by the end. At its best, A Carnival of Snackery is a sort of sampler: the bitter and the sweet. Some entries are just what you wanted. Others you might want to spit discreetly into a napkin." --
Keywords: Sedaris, David -- 1956-; Geschichte 2003-2020; Sedaris, David / Diaries; Humorists, American / 21st century / Diaries; Sedaris, David; Humorists, American; 2000-2099; Autobiographies; Diaries; Biographies; Autobiografie; Tagebuch